Эллиптические по Дуглису - Ниренбергу системы в пространствах Хермандера - Зинченко, Т.Н.; Мурач, А.А. (Український математичний журнал, 2012)
Дослiджено рiвномiрно елiптичнi в R^n за Дуглiсом – Нiренбергом системи у класi гiльбертових просторiв Хермандера H^φ, де φ — RO-змiнна функцiя скалярного аргументу. Встановлено апрiорну оцiнку розв’язкiв i дослiджено їх внутрiшню регулярнiсть. Отримано достатню умову нетеровостi цих систем. Douglis–Nirenberg systems uniformly elliptic in ℝ^n are studied in the class of Hörmander Hilbert spaces H^φ; where φ is an RO-varying function of scalar argument. An a priori estimate is established for the solutions, and their interior regularity is investigated. A sufficient condition under which these systems possess the Fredholm property is obtained.